Influence of Thermal and Mechanical Factors on the Stressed State of Large Components of Hydrogenerator-Motors - Tretyak, A.V.; Shut, A.Yu.; Gakal, P.G. (Проблеми машинобудування, 2018)
The work presented contains a detailed analysis of the existing ultimate power air-cooled hydrogenerator-motor design. Виконано детальний аналіз конструкції гідрогенератора-двигуна граничної потужності з повітряним охолодженням. Выполнен детальный анализ конструкции гидрогенератора-двигателя предельной мощности с воздушным охлаждением.